Réponses

Meilleure réponse !
2014-04-21T21:41:06+02:00
A = 2*2 = 4

B = 4*2 + 5
= 8+5
= 13

C = 4(2-3)(2+8)
= 4*(-1)*10
= -4*10
= -40

D = 3*2 - 2(5*2-15)
= 6 - 2(10-15)
= 6+2*5
= 6+10
= 16

E = 9*2²
= 9*4
= 36
H = 2*4 - 4*2
= 8-8
= 0

I = 4*4 - 4*0
= 16

J = -3*4 +10-4
= -12+6
- 6
Et voilà le reste de la réponse.
merci bcp pr tn aide
De rien ! Bon courage pour demain !
merci bcp c'est très gentille :)
2014-04-21T21:47:09+02:00
A = 2x = 2*2 =4

b = 4x+5 = 4*2 +5 = 8+5 =13

c =4 (x-3)(x+8) = 4 ( 2-3) (2+8) = 4(-1) (10) = 4(-10) = -40

d = 3x-2(5x-15) = 3 *2 -2(5*2-15) =6 -2(10-15) = 6 -2(-5) =6 +10 = 16

e = 9x² = 9(2)² = 9*4 =36

f = 7-2x = 7-2*2 = 7-4 = 3

g = 2 (3x-2) = 2(3*-2-2) = 2 (-6-2)=2 (-8)= -16

h = x (x+2) -4x = 2 (2+2) -4(2) = 2(4) -8 = 8-8 =0

i = 4x²-2x (4-x) = 4(2)² -2*2(4-2) =4(4) -4(2) =16-8 =8

j = -3x²+5x -4 = -3(2)² +5 (2) -4 = -3(4) +10 -4 = -12+10-4 = -6